Secondary battery and electric device

By using silicon carbon material and graphite in the negative electrode sheet of the secondary battery, and adding specific additives to the electrolyte to control its content range, the problems of degradation in performance and shortening of cycle life in high-temperature environments are solved, and the high-temperature circulation, high-temperature storage and gas production performance are significantly improved.

CN119786700AActive Publication Date: 2025-04-08SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411988817.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing secondary batteries show problems of degradation in high temperature environments and shortened cycle life.

Method used

By using a negative electrode current collector and an anode active material layer in the negative electrode sheet of the secondary battery, the negative electrode active material includes silicon carbon material and graphite; fluorovinyl carbonate, cyclic carbonate additives and sulfur-containing additives are added to the electrolyte, and the content range is controlled to meet a specific proportional relationship.

Benefits of technology

The high-temperature circulation, high-temperature storage and gas production performance of secondary batteries is significantly improved, and the structural stability of the negative electrode active material and the contact area of ​​the electrolyte are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223272920000121
    Figure BDA0005223272920000121
  • Figure BDA0005223272920000131
    Figure BDA0005223272920000131
  • Figure BDA0005223272920000132
    Figure BDA0005223272920000132
Patent Text Reader

Abstract

The invention discloses a secondary battery and a power utilization device, and belongs to the technical field of batteries, the particle size Dv99 of a silicon-carbon material, the mass fraction of a silicon element in a negative electrode active material, fluoroethylene carbonate, a cyclic carbonate additive and a sulfur-containing additive are controlled to meet the following relations: 7.70 < = (x * a) / [(y + z) * b] < = 62.86; and the high-temperature circulation, high-temperature storage and gas production performances of the secondary battery are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are different from primary batteries (non-rechargeable batteries). After releasing energy during discharge, they can be recharged to restore their charge, so they are reusable. Secondary batteries are widely used in portable electronic devices, electric vehicles, energy storage systems and other fields.

[0003] With the rapid development of electric vehicles, energy storage systems and other fields, higher requirements are placed on battery safety and long-cycle stability. Especially in high-temperature environments, battery storage performance and cycle stability have become key factors restricting their application. Existing secondary batteries often have problems such as performance degradation and shortened cycle life in high-temperature environments.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The object of the present invention is to overcome the shortcomings of the prior art and provide a secondary battery and an electrical device, wherein the secondary battery has excellent high-temperature cycle and high-temperature storage performance.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material and graphite;

[0007] The electrolyte includes fluoroethylene carbonate, cyclic carbonate additives and sulfur-containing additives;

[0008] The secondary battery satisfies: 7.70≤(x·a) / [(y+z)·b]≤62.86;

[0009] Wherein, x% is the mass percentage of the fluoroethylene carbonate in the electrolyte;

[0010] y% is the mass percentage of the cyclic carbonate additive in the electrolyte;

[0011] z% is the mass percentage of the sulfur-containing additive in the electrolyte;

[0012] aμm is the particle size D of the silicon-carbon material v 99;

[0013] b% is the mass fraction of silicon in the negative electrode active material.

[0014] As an implementation scheme of the present application, at least one of the following (I) to (V) is satisfied:

[0015] (I) 2≤x≤20;

[0016] (II) 0.5≤y≤3.5;

[0017] (III) 0.2≤z≤3;

[0018] (IV) 18≤a≤30;

[0019] (V)1.5≤b≤10.

[0020] As an embodiment of the present application, the secondary battery satisfies: -3≤x-2b≤4.

[0021] As an embodiment of the present application, the cyclic carbonate additive includes at least one of vinylene carbonate and vinyl ethylene carbonate; and / or

[0022] The sulfur-containing additive includes at least one of vinyl sulfate, 1,3-propane sultone, propenyl-1,3-sultone, ethylene sulfite, methylene methanedisulfonate, and 1,4-butane sultone.

[0023] As an embodiment of the present application, the mass percentage of the silicon-carbon material to the negative electrode active material is 3% to 20%.

[0024] As an embodiment of the present application, the silicon-carbon material comprises a porous carbon material and elemental silicon distributed in the pores of the porous carbon material.

[0025] As an implementation scheme of the present application, the mass fraction of silicon element in the silicon-carbon material is 45% to 65%.

[0026] As an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate with a surface coated with carbon;

[0027] The lithium iron phosphate includes Li p Fe 1-q A q PO 4 At least one of the compounds, wherein A includes at least one of Ti, Mg, and Mn, 0.9≤p≤1.1, and 0≤q≤0.2.

[0028] As an embodiment of the present application, at least one of the following (VI) to (VIII) is satisfied:

[0029] (VI) Particle size D of the positive electrode active material v 99: 3-10 μm;

[0030] (VII) The specific surface area of ​​the positive electrode active material is 5 to 12 m 2 / g;

[0031] (VIII) The powder compaction density of the positive electrode active material under a pressure of 40KN is 2 to 3.5 g / cm 3 .

[0032] As an embodiment of the present application, the electrolyte also includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bis(oxalate)difluorophosphate, lithium bis(oxalate)borate, and lithium difluorooxalateborate.

[0033] As an embodiment of the present application, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide;

[0034] The mass percentage of the lithium hexafluorophosphate in the electrolyte is 6.0% to 14.5%;

[0035] The mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3.5%.

[0036] A second aspect of the present application provides an electrical device, comprising the secondary battery described above.

[0037] The beneficial effect of the present invention is that: the present invention controls the particle size D of the silicon-carbon material v 99. The mass fraction of silicon in the negative electrode active material, as well as fluoroethylene carbonate, cyclic carbonate additives, and sulfur-containing additives satisfy the following relationship: 7.70≤(x·a) / [(y+z)·b]≤62.86; the fluoroethylene carbonate described above can be tightly coupled with the silicon in the negative electrode active material. On the one hand, it can ensure the film quality of fluoroethylene carbonate on the surface of the silicon-based negative electrode plate and inhibit the volume expansion of the silicon-based material; on the other hand, it can avoid the deterioration of storage and gas production performance caused by fluoroethylene carbonate. Cyclic carbonate additives can further improve the stability of negative electrode film formation and alleviate the volume expansion and contraction problems during charging and discharging. At the same time, sulfur-containing additives reduce side reactions produced at high temperatures and improve the gas production risk caused by the use of fluoroethylene carbonate. Particle size D of silicon-carbon material v 99 and silicon content can reduce the van der Waals force during lithium ion embedding, reduce the lithium ion deintercalation path, increase the contact area with the electrolyte, improve the structural stability of the negative electrode active material and the negative electrode sheet, and significantly improve the high-temperature cycle, high-temperature storage and gas production performance of the secondary battery. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0039] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0040] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0041] The inventors of this application have found that lithium iron phosphate (LiFePO 4 )-graphite system batteries are widely favored by the power battery market due to their long life, high safety, low cost and environmental sustainability. However, with the ultimate pursuit of end-users for endurance and fast charging capabilities, the shortcomings of lithium iron phosphate batteries in energy density and kinetic performance are becoming increasingly prominent. Compared with the theoretical gram capacity of 372mAh / g of graphite negative electrode, the theoretical gram capacity of silicon negative electrode has been greatly improved. At the same time, the lithium insertion potential of silicon negative electrode (0.4V vs.Li + / Li) is slightly higher than graphite (0.05V vs.Li + / Li), can reduce the risk of negative electrode lithium plating during charging (especially fast charging), thereby alleviating the loss of active lithium during battery cycling and avoiding the risk of internal short circuit induced by lithium dendrites. It can be seen that matching lithium iron phosphate positive electrode with silicon-based negative electrode can further improve the endurance and safety of lithium iron phosphate batteries.

[0042] However, the volume expansion problem of silicon negative electrode during the charging and discharging process and the accompanying structural collapse and interface damage will worsen the electron conduction between active particles, accelerate the consumption of electrolyte and the occurrence of side reactions at the electrode / electrolyte interface, causing irreversible capacity loss and safety risks such as gas production.

[0043] Therefore, based on the above problems, the embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material and graphite;

[0044] The electrolyte includes fluoroethylene carbonate, cyclic carbonate additives and sulfur-containing additives;

[0045] The secondary battery satisfies: 7.70≤(x·a) / [(y+z)·b]≤62.86, for example, it can be 7.7, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 62, 62.86 or a range consisting of any two of the values;

[0046] Wherein, x% is the mass percentage of the fluoroethylene carbonate in the electrolyte;

[0047] y% is the mass percentage of the cyclic carbonate additive in the electrolyte;

[0048] z% is the mass percentage of the sulfur-containing additive in the electrolyte;

[0049] aμm is the particle size D of the silicon-carbon material v 99;

[0050] b% is the mass fraction of silicon in the negative electrode active material.

[0051] The applicant of the present application has found that the volume average particle size of the negative electrode active material, the mass fraction of silicon in the negative electrode active material, and fluoroethylene carbonate, cyclic carbonate additives, and sulfur-containing additives can affect the performance of the secondary battery. v 99. The mass fraction of silicon in the negative electrode active material, as well as fluoroethylene carbonate, cyclic carbonate additives, and sulfur-containing additives satisfy the following relationship: 7.70≤(x·a) / [(y+z)·b]≤62.86. In this embodiment, fluoroethylene carbonate can be tightly coupled with the silicon in the negative electrode active material. On the one hand, it can ensure the film formation quality of fluoroethylene carbonate on the surface of the negative electrode pole piece and inhibit the volume expansion of the silicon-carbon material; on the other hand, it can avoid the deterioration of the storage and gas production performance of fluoroethylene carbonate. Cyclic carbonate additives can further improve the stability of negative electrode film formation and alleviate the volume expansion and contraction problems during charging and discharging. At the same time, sulfur-containing additives reduce side reactions produced at high temperatures and improve the gas production risk caused by the use of fluoroethylene carbonate. Particle size D of silicon-carbon material vThe content of 99 and silicon elements can reduce the van der Waals force during lithium ion embedding, reduce the lithium ion deintercalation path, increase the contact area with the electrolyte, improve the structural stability of the negative electrode active material and the negative electrode sheet, and significantly improve the high-temperature cycle, high-temperature storage and gas production performance of the secondary battery.

[0052] Among them, the particle size D of the silicon carbon material v 99 is the particle size corresponding to when the cumulative volume percentage of the silicon-carbon material reaches 99%. It should be noted that the particle size D of the silicon-carbon material of the present invention is v The test of 99 refers to GB-T19077-2016 and is tested using a particle size analysis laser diffractometer.

[0053] In one embodiment, 2≤x≤20, for example, it can be 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 or a range consisting of any two of these values. By controlling the content of fluoroethylene carbonate within this range, it is possible to promote the formation of a stable SEI film at the negative electrode, reduce the generation of hydrofluoric acid, alleviate the volume expansion of the negative electrode active material, and closely couple with the silicon in the negative electrode active material, thereby further improving the high temperature cycle, high temperature storage and gas production performance of the secondary battery.

[0054] In one embodiment, 0.5≤y≤3.5, for example, it can be 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5 or a range consisting of any two of these values. By controlling the content of the cyclic carbonate additive within this range, the film formation stability at the interface of the negative electrode plate can be improved, and the direct reaction between the electrolyte and the negative electrode active material can be effectively prevented, thereby slowing down the decomposition of the electrolyte, while reducing the side reactions between the electrolyte and the negative electrode active material, alleviating the volume expansion and contraction problems during the charge and discharge process, and further improving the high temperature cycle, high temperature storage and gas production performance of the secondary battery.

[0055] In one embodiment, 0.2≤z≤3, for example, it can be 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3 or a range consisting of any two of these values. By controlling the content of the sulfur-containing additive within this range, the shedding of active substances and the decomposition of the electrolyte can be reduced, the side reactions produced at high temperatures can be reduced, and the risk of gas production caused by the use of fluoroethylene carbonate can be improved, thereby further improving the high temperature cycle, high temperature storage and gas production performance of the secondary battery.

[0056] In one embodiment, 18≤a≤30, for example, it can be 18, 20, 22, 24, 25, 26, 28, 30 or a range consisting of any two of these values. By controlling the particle size D of the silicon-carbon material v99 Within this range, the wettability of the electrolyte can be improved, the electrode impedance can be reduced, the lithium precipitation phenomenon can be improved, the migration rate of lithium ions can be increased, and the high-temperature cycle, high-temperature storage and gas production performance of the secondary battery can be further improved.

[0057] In one embodiment, 1.5≤b≤10, for example, it can also be 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two of these values. By controlling the mass fraction of silicon in the negative electrode active material within this range, during the operation of the battery, the silicon element reacts with the byproduct F in the electrolyte. – Combined with HF, it avoids HF from destroying the interface, thereby alleviating the side reaction between the negative electrode interface and the electrolyte solvent, achieving the effect of inhibiting gas production. At the same time, the addition of silicon-carbon materials is also beneficial to the improvement of the energy density of secondary batteries.

[0058] In one embodiment, the secondary battery satisfies: -3≤x-2b≤4, for example, it can be -3, -2, -1, 0, 1, 2, 3, 4 or a range consisting of any two of these values. By controlling x-2b within this range, the fluoroethylene carbonate can be more effectively coupled with the silicon element in the negative electrode active material, promote the formation of a more uniform and dense SEI film, effectively inhibit the volume expansion and interface passivation of the negative electrode active material, avoid the deterioration of the storage and gas production performance of the fluoroethylene carbonate, and further improve the high temperature cycle, high temperature storage and gas production performance of the secondary battery.

[0059] In one embodiment, the cyclic carbonate additive includes at least one of vinylene carbonate and vinyl carbonate. The above additive can improve the film forming stability.

[0060] The sulfur-containing additive includes at least one of vinyl sulfate, 1,3-propane sultone, propenyl-1,3-sultone, ethylene sulfite, methylene methane disulfonate, and 1,4-butane sultone. The above-mentioned additive can inhibit the decomposition and gas generation of the electrolyte.

[0061] In one embodiment, the mass percentage of the silicon-carbon material in the negative electrode active material is 3% to 20%, for example, it can be 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20% or a range consisting of any two of these values. By controlling the content of the silicon-carbon material in the negative electrode active material within this range, the energy density of the secondary battery can be effectively improved.

[0062] In one embodiment, the graphite includes at least one of natural graphite and artificial graphite.

[0063] In one embodiment, the mass percentage of the graphite in the negative electrode active material is 80% to 97%, for example, it can be 80%, 82%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 97% or a range consisting of any two values ​​therein. The graphite content within the above range can improve the cycle stability of the negative electrode sheet and enhance the long cycle performance of the battery.

[0064] In one embodiment, the silicon-carbon material comprises a porous carbon material and elemental silicon distributed in the pores of the porous carbon material, so that the energy density of the negative electrode active material can be increased while also suppressing the expansion of the negative electrode material.

[0065] In one embodiment, the mass fraction of silicon in the silicon-carbon material is 45% to 65%, for example, it can be 45%, 46%, 48%, 50%, 52%, 55%, 56%, 58%, 60%, 62%, 64%, 65% or a range consisting of any two of these values. By controlling the mass fraction of silicon in the silicon-carbon material within this range, the stability of the silicon-carbon material can be taken into account and the expansion of the silicon-carbon material during the cycle can be suppressed.

[0066] In one embodiment, the positive electrode sheet includes a positive current collector and a positive active material layer on at least one surface of the positive current collector, the positive active material layer includes a positive active material, and the positive active material includes lithium iron phosphate coated with carbon on the surface. In some embodiments, the carbon content accounts for 1% to 3.5% by mass of the positive active material, for example, it can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or a range consisting of any two of these values, so as to take into account the stability and conductivity of the positive active material.

[0067] In one embodiment, the lithium iron phosphate comprises Li p Fe 1-q A q PO 4 At least one of the compounds, wherein A includes at least one of Ti, Mg, and Mn, 0.9≤p≤1.1, 0≤q≤0.2, when element A is doped into lithium iron phosphate, the conductivity of the positive electrode active material can be further improved, the crystal structure of lithium iron phosphate can be effectively stabilized, the stability of lithium iron phosphate can be improved, and the resistance to lithium ion insertion and extraction can be reduced.

[0068] In one embodiment, the particle size D of the positive electrode active material is v 99 is 3 to 10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range consisting of any two of these values. The particle size D of the positive electrode active materialv 99 When it is within this range, it is conducive to the uniform distribution and transmission of lithium ions, thereby improving the cycle stability and consistency of the battery.

[0069] Among them, the particle size D of the positive electrode active material v 99 is the particle size corresponding to when the cumulative volume percentage of the positive electrode active material reaches 99%. It should be noted that the test of Dv99 of the positive electrode active material of the present invention refers to GB-T 19077-2016 and is tested using a particle size analysis laser diffractometer.

[0070] In one embodiment, the specific surface area of ​​the positive electrode active material is 5 to 12 m 2 / g, for example, it can be 5m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g or a range consisting of any two of the values, when the specific surface area of ​​the positive electrode active material is within this range, the contact area with the electrolyte can be increased, the wettability of the electrolyte can be increased, and the transmission rate of lithium ions can be increased.

[0071] It should be noted that in the present invention, a specific surface area and pore size distribution measuring instrument is used to test the specific surface area of ​​the negative electrode active material, and the test standard is GB / T 19587-2017 gas adsorption BET method.

[0072] In one embodiment, the powder compaction density of the positive electrode active material under a pressure of 40KN is 2 to 3.5 g / cm 3 , for example, it can be 2g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.2g / cm 3 , 3.5g / cm 3 Or a range consisting of any two of the values, the positive electrode active material has a high compaction density and a high filling degree between particles, which is not only conducive to improving the processing performance of the positive electrode active material, but also can effectively improve the energy density of the battery. The compaction density can be measured according to GB / T 24533-2009.

[0073] In one embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bis(oxalatodifluorophosphate), lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

[0074] In one embodiment, the lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0075] The mass percentage of the lithium hexafluorophosphate in the electrolyte is 6.0% to 14.5%, for example, it can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 14.5% or a range consisting of any two values ​​therein.

[0076] In one embodiment, the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3.5%, for example, 0.5%, 0.8%, 1%, 1.5%, 2.5%, 3%, 3.5% or a range consisting of any two of these values.

[0077] The present application adopts a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide as lithium salt, which can improve the lithium ion migration number and antioxidant performance, and has good aluminum foil passivation ability, has good matching with the positive electrode active material and negative electrode active material system of the present application, improves stability, repairs the electrode / electrolyte interface, improves ionic conductivity, and promotes the conduction of lithium ions in the bulk phase.

[0078] In one embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate (MPC), diphenyl carbonate (DPhC), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and γ-butyrolactone (γ-GBL).

[0079] In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0080] In one embodiment, the positive electrode active material layer further includes a conductive agent and a binder.

[0081] In the present application, the negative electrode current collector includes copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0082] In one embodiment, the negative electrode active material layer further includes a conductive agent and a negative electrode binder.

[0083] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0084] In one embodiment, the negative electrode binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.

[0085] In the secondary battery mentioned in the present application, in order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode, and the separator includes at least one of a polypropylene separator and a polyethylene separator.

[0086] In one embodiment, the secondary battery may include an outer package, which can be used to encapsulate the electrode assembly and the electrolyte.

[0087] In one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0088] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0089] An embodiment of the present application provides an electrical device, comprising the secondary battery described above.

[0090] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0091] The present application is further described below with specific embodiments:

[0092] Example 1

[0093] A method for preparing a secondary battery comprises the following steps:

[0094] (1) Preparation of positive electrode sheet

[0095] Preparation of positive electrode active material: prepare a mixed solvent A with ethanol and water in a volume ratio of 1:3; weigh lithium hydroxide, iron phosphate, diammonium hydrogen phosphate, and titanium dioxide according to the molar ratio of Li:Fe:P:Ti of 1:1:1:0.05, add lithium hydroxide, iron phosphate, diammonium hydrogen phosphate, and titanium dioxide to the mixed solution under nitrogen protection, stir evenly, add ammonia solution to adjust the pH to 9.8, hydrothermally react at 180°C for 5h, cool naturally to room temperature, filter, wash (wash 3 times with distilled water, then wash 3 times with ethanol) and dry (vacuum dry at 80°C) to obtain a precursor.

[0096] The precursor and glucose were mixed evenly in a mass ratio of 98:2, and then the mixture was sintered at 750°C for 6 hours under a nitrogen atmosphere to obtain a positive electrode active material, wherein the positive electrode active material is lithium iron phosphate (LiFeTi 0.05 PO 4 ), the carbon content accounts for 2% of the mass percentage of the positive electrode active material, and the specific surface area is 9.8m 2 / g,D v 99 is 6μm, and the compacted density of the powder under a pressure of 40KN is 2.4g / cm 3 ;

[0097] The positive electrode active material, the conductive agent acetylene black (Super P) and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of LiFePO 4 :Super P:PVDF=94:3:3 were mixed evenly and dispersed evenly in 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed slurry was coated on both sides of the aluminum foil and then baked and rolled (the compacted density was 2.6g / cm 3 ), and then cut into strips and sheets to obtain the positive electrode sheet.

[0098] (2) Preparation of negative electrode sheet

[0099] Preparation of silicon carbon material: Porous carbon material (specific surface area 1600m 2 / g) was put into a fluidized bed reactor, nitrogen was introduced to make the porous carbon in a fluidized state, the temperature was controlled to be 650° C., the pressure of monosilane gas was 0.4 MPa, monosilane gas was introduced to perform chemical vapor deposition, so that elemental silicon was deposited in the pores of the porous carbon material, and the content of silicon element was controlled to be 50wt%, thereby preparing a silicon-carbon material;

[0100] The negative electrode active material artificial graphite (AG), silicon carbon material (silicon mass fraction of 50%, particle size index Dv99 of 22μm), conductive agent acetylene black (Super P), carbon nanotubes (CNT) and binder SBR are mixed uniformly according to the mass ratio of AG: silicon carbon material: Super P: CNT: SBR = 87:7:2:1:3, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the copper foil, and then baked and rolled (the compaction density is 1.5g / cm 3 ), and then cut into strips and sheets to obtain the negative electrode sheet.

[0101] (3) Preparation of electrolyte

[0102] At room temperature, in a glove box filled with argon (H 2 O<1ppm,O 2 <1ppm), non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate and ethyl acetate were mixed into a mixed solvent in a mass ratio of 30:40:30, and then Molecular sieve to remove water and set aside;

[0103] Lithium salt (LiPF 6 + 1LiFSI) was added to the mixed solvent, stirred continuously and cooled to finally obtain a colorless transparent liquid;

[0104] Fluoroethylene carbonate (FEC) equivalent to 7.0% of the total mass of the electrolyte, 1.5% of vinylene carbonate (VC) and 0.5% of 1,3-propane sultone (sulfur-containing additive, PS) were added to obtain the electrolyte, LiPF 6 , LiFSI account for 12.8% and 1% of the total mass of the electrolyte respectively.

[0105] (4) Assembly of secondary batteries:

[0106] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator being placed between the positive and negative electrode sheets. A bare battery cell is obtained through winding, hot pressing, Hi-pot testing, and tab welding. The bare battery cell is encapsulated in an outer packaging aluminum-plastic film and baked in an oven at 100±5°C for 48h. The prepared electrolyte (injection coefficient is 4.0g / Ah) is injected into the dried battery, allowed to stand, formed, and capacity divided to obtain a secondary battery.

[0107] The specific parameters of this embodiment are shown in Table 1.

[0108] Embodiments 2 to 6

[0109] The difference between Examples 2 to 6 and Example 1 is that the content of FEC is adjusted.

[0110] Embodiments 7 to 10

[0111] The difference between Examples 7 to 10 and Example 1 is that the content of VC is adjusted.

[0112] Examples 11-12

[0113] The difference between Examples 11 and 12 and Example 1 is that the content of VC and the type of sulfur-containing additive (PST, i.e., propenyl-1,3-sultone, MMDS, i.e., methylene methane disulfonate) are adjusted.

[0114] Embodiments 13 to 15

[0115] The difference between Examples 13 to 15 and Example 1 is that the amount of the sulfur-containing additive is adjusted.

[0116] Embodiments 16 to 18

[0117] The difference between Examples 16 to 18 and Example 1 is that the particle size D of the silicon-carbon material is adjusted. v 99.

[0118] Examples 19 to 22

[0119] The difference between Examples 19 to 22 and Example 1 is that the mass fraction of silicon in the negative electrode active material is adjusted by adjusting the ratio of the silicon-carbon material to the artificial graphite.

[0120] Examples 22 to 27

[0121] The difference between Examples 22 to 27 and Example 1 is that the type and amount of lithium salt are adjusted.

[0122] Embodiments 28 to 30

[0123] The difference between Examples 28 to 30 and Example 1 is that the particle size D of the positive electrode active material is changed by ball milling and sieving the positive electrode active material. v 99, thereby changing the specific surface area of ​​the positive electrode active material and the powder compaction density under a pressure of 40KN.

[0124] Comparative Examples 1 to 4

[0125] The preparation process is the same as that of Example 1, except that the amount of FEC added, the proportion of silicon-carbon material added, the content of VC and the particle size D of the silicon-carbon material are adjusted respectively. v 99. VC content and sulfur-containing additives content.

[0126] Table 1

[0127]

[0128]

[0129] Table 2

[0130]

[0131] Battery performance test

[0132] Room temperature DCR test: At 25±2°C, the secondary batteries obtained in the embodiments and comparative examples were charged to 3.65V at 1C, then discharged at 1C for 30min, adjusted to 50% SOC, and then discharged at 5C constant current pulse for 10s and charged for 10s. DCR was calculated as (voltage before pulse discharge – voltage after pulse discharge) / discharge current*100%. The recorded results are shown in Table 3.

[0133] Observation of lithium plating at the interface: At 25±2°C, the secondary batteries obtained from the embodiments and comparative examples were subjected to charge and discharge cycle tests in the range of 2.5 to 3.65V with a charge and discharge rate of step charge (peak 5C, 10% to 80% SOC, ≤10min). The batteries were disassembled after 10 cycles to observe lithium plating at the negative electrode. The recorded results are shown in Table 3 (mild lithium plating: the lithium plating area on the surface of the negative electrode piece accounts for 5% to 20%; moderate lithium plating: the lithium plating area on the surface of the negative electrode piece accounts for 20% to 40%).

[0134] Normal temperature cycle performance test: At 25±2°C, the secondary batteries obtained in the embodiment and the comparative example were subjected to charge and discharge cycle tests at a charge and discharge rate of 1C / 1C in the range of 2.5-3.65V, and the battery's first week discharge capacity and the discharge capacity after 1000 cycles were recorded. After 1000 cycles of fast charge cycles, the battery was disassembled to observe the lithium deposition of the negative electrode. The capacity retention rate of 1000 weeks = 1000 weeks of discharge capacity / first week discharge capacity*100%, and the recorded data is shown in Table 3.

[0135] High temperature cycle performance test: At 45±2°C, the secondary batteries obtained in the embodiments and comparative examples were subjected to charge and discharge cycle tests at a charge and discharge rate of 1C / 1C in the range of 2.5 to 3.65V, and the first week discharge capacity and the discharge capacity after 1000 cycles of the battery were recorded. The capacity retention rate of 1000 cycles = 1000 weeks discharge capacity / first week discharge capacity*100%, and the recorded data are shown in Table 3.

[0136] High temperature storage performance: The secondary batteries obtained in the examples and comparative examples were placed at 60±2°C, and the charge and discharge test was performed at a charge and discharge rate of 1C / 1C in the range of 2.5 to 3.65V, and the first week discharge capacity of the battery was recorded. After that, the battery was stored at 60±2°C for 90 days, and the charge and discharge test was performed again and the discharge capacity was recorded. High temperature storage capacity retention rate = discharge capacity after 90 days / first week discharge capacity*100%, and the recorded data is shown in Table 3.

[0137] High temperature gas generation test: The secondary batteries obtained in the examples and comparative examples were charged at 25±2°C at a constant current rate of 1C to 3.65V, and then charged at a constant voltage of 3.65V to a current equal to 0.05C, so that they were in a fully charged state of 3.65V. The volume of the fully charged battery before storage was tested and recorded as V 0 ; Then place the fully charged battery in a 60±2℃ oven. After 14 days, take out the battery and immediately test its volume after storage and record it as V 1 Volume expansion rate = (V 1 –V 0 ) / V*100%, the results are shown in Table 3.

[0138] Table 3

[0139]

[0140] As can be seen from Table 1, the present invention can significantly improve the high temperature cycle, high temperature storage and gas production performance of the secondary battery by controlling the volume average particle size of the negative electrode active material, the mass fraction of the silicon element in the negative electrode active material, and the fluoroethylene carbonate, cyclic carbonate additives, and sulfur-containing additives to satisfy the following relationship: 7.70≤(x·a) / [(y+z)·b]≤62.86.

[0141] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material and graphite; The electrolyte includes fluoroethylene carbonate, cyclic carbonate additives and sulfur-containing additives; The secondary battery satisfies: 7.70≤(x·a) / [(y+z)·b]≤62.86; Wherein, x% is the mass percentage of the fluoroethylene carbonate in the electrolyte; y% is the mass percentage of the cyclic carbonate additive in the electrolyte; z% is the mass percentage of the sulfur-containing additive in the electrolyte; aμm is the particle size D of the silicon-carbon material v 99; b% is the mass fraction of silicon in the negative electrode active material.

2. The secondary battery according to claim 1, characterized in that: Satisfy at least one of the following (I) to (V): (Ⅰ)2≤x≤20; (Ⅱ)0.5≤y≤3.5; (Ⅲ)0.2≤z≤3; (Ⅳ)18≤a≤30; (Ⅴ)1.5≤b≤10。 3. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies: -3≤x-2b≤4.

4. The secondary battery according to claim 1, characterized in that: The cyclic carbonate additive includes at least one of vinylene carbonate and vinyl carbonate; and / or The sulfur-containing additive includes at least one of vinyl sulfate, 1,3-propane sultone, propenyl-1,3-sultone, ethylene sulfite, methylene methanedisulfonate, and 1,4-butane sultone.

5. The secondary battery according to claim 1, characterized in that: The mass percentage of the silicon-carbon material to the negative electrode active material is 3% to 20%.

6. The secondary battery according to claim 5, characterized in that: The silicon-carbon material comprises a porous carbon material and elemental silicon distributed in the pores of the porous carbon material.

7. The secondary battery according to claim 6, characterized in that: The mass fraction of silicon element in the silicon-carbon material is 45% to 65%.

8. The secondary battery according to claim 1, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes lithium iron phosphate with a surface coated with carbon; The lithium iron phosphate includes Li p Fe 1-q A q At least one of the compounds of PO4, wherein A includes at least one of Ti, Mg, and Mn, 0.9≤p≤1.1, and 0≤q≤0.

2.

9. The secondary battery according to claim 8, characterized in that: Satisfy at least one of the following (VI) to (VIII): (VI) Particle size D of the positive electrode active material v 99: 3-10 μm; (VII) The specific surface area of ​​the positive electrode active material is 5 to 12 m 2 / g; (VIII) The powder compaction density of the positive electrode active material under a pressure of 40KN is 2 to 3.5 g / cm 3 .

10. The secondary battery according to claim 1, characterized in that: The electrolyte also includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium difluorophosphate, lithium tetrafluorophosphate, lithium bis(oxalatodifluorophosphate), lithium bis(oxalatoborate), and lithium difluorooxalatoborate.

11. The secondary battery according to claim 10, characterized in that: The lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; The mass percentage of the lithium hexafluorophosphate in the electrolyte is 6.0% to 14.5%; The mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.5% to 3.5%.

12. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Negative pole piece, electrochemical device and electronic device

    CN116802852A

  • Negative plate and battery

    CN118156412A

  • Lithium ion battery

    CN119170876A

  • Composite particle, negative electrode active material, and lithium-ion secondary battery

    US20240279064A1

Cited By

  • Secondary battery and electric device

    WO2026144839A1